Weight training - McNab, Chris, 1970- (Broomall, PA : Mason Crest Publishers, 2004)
Recounts the history, rules and equipment of weight lifting, physical and mental preparation required, common injuries, and how to pursue a career in weight lifting.
The basics of weight training -- A strong mind -- Preparing the body -- Safe weight training -- Treating common injuries -- Professional weight sports.
Includes bibliographical references (p. 62) and index.
Keywords: Weight training -- Juvenile literature; Weight training injuries -- Juvenile literature; Weight lifting; Sports injuries